2020
DOI: 10.1016/j.msard.2020.102008
|View full text |Cite
|
Sign up to set email alerts
|

Which is the best PML risk stratification strategy in natalizumab-treated patients affected by multiple sclerosis?

Abstract: Background: The risk of progressive multifocal leukoencephalopathy (PML), a brain infection caused by John Cunningham virus (JCPyV), is the main limitation to the use of natalizumab, highly effective in the treatment of relapsing remitting multiple sclerosis (RRMS) patients. Establishing the PML risk against expected benefits represents an obligatory requirement of MS treatment algorithm. In order to achieve this goal, the aims of this study were to establish if JCPyV-DNA detection and non-coding control regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…In the two patients with PML, both CSF and plasma were strongly positive for JCPyV genomes when either the bulk biofluid or the EV fraction was tested. Consistent with other reports of viral genomes in EV, only a fraction of the total genome copy numbers were found to be associated with the EV [ 30 , 31 ]. It is unclear whether this is because there were fewer viral genomes in the EV compared with the total or whether this represents a loss of EV during processing, which included size-exclusion chromatography and ultrafiltration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the two patients with PML, both CSF and plasma were strongly positive for JCPyV genomes when either the bulk biofluid or the EV fraction was tested. Consistent with other reports of viral genomes in EV, only a fraction of the total genome copy numbers were found to be associated with the EV [ 30 , 31 ]. It is unclear whether this is because there were fewer viral genomes in the EV compared with the total or whether this represents a loss of EV during processing, which included size-exclusion chromatography and ultrafiltration.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, choroid plexus epithelial cells play an important role in communicating between the blood and the brain using EV [ 29 ]. Several groups have shown that EV harbor JCPyV genomes both in vivo and in vitro and contribute significantly to virus invasion of naĂŻve cells [ 30 , 31 ]. EV are also capable of carrying mutant viruses that can only infect cells when associated with these vesicles [ 13 , 14 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSIF counselled caution in the use of higher efficacy DMTs where rates of Covid-19 disease are high, with retreatments with anti-CD20 agents or cladribine tablets recommended when a prevailing high level of local Covid-19 infection has reduced. The patient's individualised risk of progressive multifocal leukoencephalopathy (PML; Bloomgren et al, 2012;Prezioso et al, 2020) should be considered in parallel with consideration of local Covid-19 infection rates before starting natalizumab, and the use of alemtuzumab was recommended only when Covid-19 rates are low. The MSIF also added a note of caution to the use of anti-CD20 DMT therapy for patients with primary progressive MS (PPMS) at higher levels of disability, as the likelihood of comorbidity in this population may complicate a Covid-19 infection further during the use of this treatment.…”
Section: Current International Expert Opinionmentioning
confidence: 99%
“…Natalizumab, a monoclonal antibody (McAb) mainly used in treatment of relapsing-remitting MS, can prevent leukocyte adherence and blocks integrin α-4 on ECs, thereby protecting the BBB (Haarmann et al, 2015). However, as an efficient inflammatory suppressant, it also inhibits immune surveillance and leads to progressive multifocal leukoencephalopathy (PML), an infectious disease caused by John Cunningham virus (Prezioso et al, 2020), which unfortunately restricts its clinical application.…”
Section: Multiple Sclerosismentioning
confidence: 99%